Building a Justice System for the Defence of Human Rights in Timor-Leste (A Contribution to Judicial Reform in a Democratic State of Law) - Hercus Pereira dos Santos (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Timor-Leste, a newly independent state, was declared a democratic state under the rule of law and respecting human dignity as a result of the struggle for the right to self-determination and human rights. In the process of building Timor-Leste as a state under the rule of law, Timor-Leste still faces many challenges, especially related to the lack of qualified human resources in all sectors, including justice and human rights. Basically, the rule of law means that the state is based on law. Law is a fundamental part of building an organized and organized state, while Timor-Leste chooses to follow the doctrine of civil law from continental Europe as a logical consequence inherited from Portuguese law, which states that law must be written, contained in a legal document, the constitution, codes, or in writing. But the state must also, beyond the supremacy of law, respect human rights issues. This means that Timor-Leste is a state governed by the rule of law, seeking to respect and value human rights. Respect for and appreciation of human rights is enshrined in the Constitution of Timor-Leste. The interpretation of fundamental rights in Timor-Leste must be in harmony with the Universal Declaration of Human Rights. The State is not based solely on law (as a state governed by law), but more than that, it is based on human rights, on the Universal Declaration of Human Rights; on respect for the dignity of the human person. Regarding the issue of justice, the Timor-Leste justice system must respect and value human rights. That is, every act of the Timor-Leste justice system must be applied in accordance with the Universal Declaration of Human Rights, with the primary objective of respecting and valuing human rights.